Epithelial-Myoepithelial Carcinoma of the Breast with Rhabdoid Features. (7th October 2020) - Grenier, Karl; Altinel, Gulbeyaz; Dastani, Zari; Omeroglu, Atilla
Abstract : Epithelial-myoepithelial carcinoma of the breast is a rare biphasic tumor composed of intermixed malignant epithelial and myoepithelial components. Myoepithelial cells are known to adopt varied morphologies, including spindle, chondroid, clear cell, and rhabdoid morphologies, and can represent a diagnostic challenge when isolated on biopsy. Rhabdomyosarcoma, phyllodes tumor, metaplastic carcinoma, and myoepithelial carcinoma are primary breast tumors that all have been shown to exhibit rhabdoid features, whether representing true differentiation or morphological mimic. We here report an epithelial-myoepithelial carcinoma of the breast with rhabdoid features in a 76-year-old woman. The rhabdoid-appearing myoepithelial cells are negative for myogenin, consistent with a rhabdoid-like morphology rather than a true rhabdoid differentiation, comparably to previously described myoepithelial carcinoma with rhabdoid features. To our knowledge, this is the first reported case of epithelial-myoepithelial carcinoma of the breast with rhabdoid features and thus adds another entity to the differential diagnosis of breast lesions with rhabdoid features.